Il museo di antropologia come museo culturale : il caso del MOA di Vancouver - C. Gualtieri (2011)
The essay explores the native collections in The Museum of Anthropology at the University of British Columbia, and analyses the policies adopted by the Museum in recent years as regards the issues of "Native Title","Cultural Property", and "Repatriation". The essays highlights the feature of MOA as cultural museum, by pointing to interesting changes in Anthropology in connection with the cultures of the First Nations of British Columbia.